Synthesis and characterization of cobalt oxide by aqueous gel-casting technique as catalyst precursor for NaBH4 hydrolysis - Ho, Xu En (2015)
High demand of energy caused a rapid depletion of energy resources in the world, resulting in the search for alternative clean energy resources. Clean energy generation techniques have been introduced. One of them is the use of fuel cell and hydrogen as its clean energy fuel. Methods to generate hydrogen have been the attention. For instance, through the hydrolysis of chemical hydrides, one can generate hydrogen. With the aid of catalyst, the hydrolysis can be accelerated. Methods to fabricate catalysts are also a hot topic recently. Cobalt based catalyst precursors have proved to be efficients. In this project, nano-powders of Co3O4 were synthesized by an effective gel-casting technique. The nano-powder was used as catalyst precursor for the hydrolysis of sodium borohydride (NaBH4). The effect of molar ratio of monomer to metal nitrates, different calcination temperatures, dwelling time and weight percentages of initiator based on monomer, on the catalytic performance and particle size were investigated in detail. The phase characterizations of cobalt oxide were determined by X-ray diffraction (XRD) using Cu Kα radiation at room temperature. Morphology of cobalt oxide powders was studied using Transmission Electron Microscopy (TEM) and the results indicate that particle size decreases as both the molar ratio of monomer to metal nitrates and the weight percentage of initiator APS on organic monomer increase. The hydrogen generation rate from hydrolysis of NaBH4 with cobalt oxide nano-powders had been investigated. The XRD results showed that the phase of the as-synthesized CO series powder matched the cubic normal spinel structure of Co3O4; The Hydrogen Generation experiment shows that the catalytic performance of as-synthesized nano-spherical Co3O4 calcined at 600oC for 2 h in air shows the highest performance and the maximum Hydrogen Generation Rate (HGR) that hydrolysis over CO4 at 600oC is 422 mL min-1 (15mg cat.)-1 when the APS is 6wt.% on monomer AM.